The Influence of Position on Leg Movements and Kicks in Older Infants With Spina Bifida. Issue 4 (2016) - Chapman, David
Abstract : Purpose: The purpose of this study was to describe the frequency with which infants with lumbar or sacral spina bifida (SB) move their legs or kick when they are 7 months and older while in the supine position, seated in a conventional infant seat (CS), and seated in a specially designed infant seat (SDIS). Methods: The spontaneous leg movements of 9 infants with lumbar or sacral SB were videotaped once per month for 4 months in each position. Results: Infants generated significantly more leg movements when seated in the SDIS than in the CS and significantly more kicks in the SDIS than in the other 2 positions. Conclusions: The movement context influences the ability of older infants with SB to move their legs and to kick. Abstract : The purpose of this study was to describe the frequency with which infants with lumbar or sacral spina bifida move their legs or kick when supine, seated in a conventional infant seat, and seated in a specially designed infant seat.